Gender Differential Item Functioning (GDIF) Analysis in Iran's University Entrance Exam - Soodeh Bordbar (English Language in Focus (ELIF), 2020)
The significant aspect of validity defines what the test score actually and potentially represents, especially to the causes of invalidity concepts of fairness, bias, injustice, and inequity. The Differential Item Functioning (DIF) examines the test items to define test fairness and to examine the validity of educational tests. If gender plays a major role in the testing items, this will lead to bias. This research examines the validity of a test for high-stakes and discusses gender's role as a bias in different linguistic tests, to explore validity and DIF analytics. To get a DIF analysis, the Rasch model had been used as a university entry requirement for English language studies for five thousand people taking part, who'd been randomly selected from a group of examiners participating in the National University Entrance Exam for Foreign Languages (NUEEFL), i.e., English literature, Teaching, and Translation. The test results indicated that the test scores are not free of construct-irrelevant variance, and certain inaccurate items have been modified following the fit statistics guidelines. Overall, NUEEFL's fairness was not clarified. These findings had been some advantage to test designers, stakeholders, administrators, and teachers through that kind of psychometric test. Then it suggested the future administering criteria and bias-free tests and teaching materials.